THE STRUCTURE AND TERRITORIAL ORGANIZATION OF THE NATIONAL EDUCATIONAL SERVICES MARKET IN THE SPHERE OF TOURISM - Орлова, Марія (Human Geography Journal, 2015)
The article is analyzed the prerequisites for the formation anddevelopment prospects of the Ukranian education market in the sphere of tourism. The quantitative factors of subject functionproviding educational services in the sphere of tourism and their territorial organization are considered. The short description ofindividual institutions of higher education in our country included in educational activities in the sphere of tourism are given. Thesystem of higher education standards as the mechanism for monitoring and improving the quality of educational services is studied.The labor-market in the tourism industry of Ukraine till 2012 and its relationship to the modern market of educational services isanalyzed.